# math,correction from previous post

posted by .

can someone please correct this for me thanks.

simplify:

7sqrt(7x) + 5 sqrt (7x)

My work:

(7+5)sqrt (7x)

12sqrt (7x)

is this correct?

yup

so i don't have to take out the x from the radicand

Nope.

7x + 5x = 12x

No matter what "x" is.

## Similar Questions

1. ### math

how would you simplify this equation: y = (x+3)/[(4-sqrt(16+h))] please help me! you have three variables. I am not certain "simplify" is an appropriate term here. ohhhh it was my mistake. I meant: y = h/[(4-sqrt(16+h))] y = h/[(4-sqrt(16+h))] …
2. ### math,correction

Can someone help me with these...plz Simplify 2radical (12) + 4 radical (27) if i simplify radical (12) i get 2radical (3) then if i simplify radical (27) i get 3radical (3). so now i don't know if i'm doing this correctly or how to …
3. ### math,correction

i am really trying is this correct. solve: 5(x-2)^2 = 3 MY ANSWER THAT I GOT IS: X = 2 +- (SQRT (3) )/(5) no. 5(x-2)^2 = 3 (x-2)^2 = 3/5 x-2 = +- sqrt (3/5) x= 2 +- sqrt (3/5) so the whole fraction of 3/5 is inside the sqrt yes
4. ### math,correction

is this correct: solve by using the quadratic formula 5x^2+x=3 what i keep getting is this: (-1 +/- sqrt 61)/(10) or should i reduce the denominator to 5 or is my whole answer incorrect?
5. ### math,correction

simplify: 7sqrt(7x) + 5 sqrt (7x) My work: (7+5)sqrt (7x) My answer: 12sqrt (7x) is this correct?
6. ### math,correction

simplify: sqrt ((7)/(100)) my work: 7 = 1sqrt (7) 100= 10 sqrt (1) (1)/(10) sqrt (7) my answer: (sqrt (7))/(10) Your answer is right but your statements: 7 = 1sqrt (7) 100= 10 sqrt (1) make no sense. how can sqrt(7)=7 ?
7. ### Math Help please!!

Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
8. ### Algebra

Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
9. ### Algebra - sqrts

Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
10. ### Algebra

How do you simplify this? -16^(1/4) Someone showed me like this: (-1)(16^(1/4))=(-1)(2)=-2 But others said ... -16^(1/2)= 4i 4i^(1/2) or the sqrt of 4i=sqrt of 4 times sqrt of i Final answer: 2 times sqrt of i What is the correct answer

More Similar Questions

Post a New Question